Case Report: Inferior Bilobectomy for Lung Cancer to Allow Weaning From Veno-Venous Extracorporeal Membrane Oxygenation - Signore, Francesca; Brascia, Debora; Schiavone, Marcella; De Iaco, Giulia; Panza, Teodora; De Palma, Angela; Murgolo, Francesco; Civita, Antonio; Di Mussi, Rosa; Grasso, Salvatore; Marulli, Giuseppe (Frontiers in Surgery, 2021)
In recent years, veno-venous extracorporeal membrane oxygenation has allowed complex lung and airways resections in patients with a compromised peri-operative respiratory function. In the following report, we present a case of successful weaning from v-v ECMO in a patient who underwent an inferior bilobectomy for lung cancer.